Echocardiographic findings of children with Down syndrome (Annals of Medical Research, 2024)
Aim: Down syndrome is the most common well-known chromosomal disorder. The incidence of congenital heart disease (CHD) in these patients is high and it is the most important cause of mortality. In this study, we reviewed the comorbid CHDs and their characteristics in patients with the diagnosis of Down syndrome. We compared our results with the results of studies conducted in different regions of our country in different years.Materials and Methods: Between January 2020 and December 2022, data from a total of 385 patients (175 females, 210 males) with Down syndrome were evaluated. The age of the mothers at the time of delivery and the availability of prenatal diagnosis information in accessible patients were determined.Results: Of 385 patients with Down syndrome, 38.2% (n=147) had CHD. Among patients with CHD, 57 patients had atrioventricular septal defect (AVSD)(38.7%), 35 patients had perimembranous ventricular septal defect (23.8%), 24 patients had secundum atrial septal defect(16.3%), 8 patients had patent ductus arteriosus(5.4%), and 10 patients without AVSD had CHD with multiple left-to-right shunts (6.8%). The most common cyanotic CHD was tetralogy of Fallot (n=7, 4.7%). Complete AVSD was present in 63.1% of AVSD patients. CHD was present in 36.2% of boys and 40.6% of girls. Among all female patients, 17.1% had AVSD, while this rate was 12.8% among all male patients (p
Keywords: Down syndrome; Congenital heart disease; Prenatal diagnosis